From face-to-face to online foreign language teaching: Capitalising on lessons learned during COVID 19 - Nicolaou, Anna; Nikitaki, Stavroula; Salomi Papadima-Sophocleous (My University, 2022)
The COVID-19 pandemic transformed the educational landscape overnight. Face-to-face instruction urgently gave its place to online teaching, forcing educators to adopt tools and techniques they had never used before and creating doubts regarding its effectiveness. However, it also improved teachers' and students' digital skills creating new perceptions towards technology-enhanced teaching. This study maps the use of technology in online FL teaching in Greek Primary Schools during the first COVID-19 lockdown. Using a mixed methods approach, an online questionnaire, and interviews, it records the tools and the ways they were used, the pedagogical choices made, the challenges and the factors that affected the quality of online teaching during the crisis. Based on the lessons learned and the literature, this chapter aims to contribute to sharing the knowledge gained and provide recommendations to the state, schools, and teachers for the preparation and delivery of quality online or blended learning in the future.